2017
DOI: 10.3390/su9030431
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Land Use Changes in a Coastal Reclaimed Area with Dynamic Shorelines

Abstract: Abstract:Reclamation is capable of creating abundant land to alleviate the pressure from land shortages in China. Nevertheless, coastal reclamation can lead to severe environmental degradation and landscape fragmentation. It is quite important to monitor land use and cover change (LUCC) in coastal areas, assess coastal wetland change, and predict land use requirements. The siltation of tidal flats will result in the dynamic growth and continuous expansion of coastal areas. Therefore, the process of land change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…With the development and application of computer science and geographic information system (GIS) technology, research on land use spatial layout simulation models has rapidly increased [ 15 , 16 , 17 , 18 ]. Researchers have used a variety of simulation models to simulate future land use in terms of the quantitative characteristics and spatial layout, including a multi-agent system (MAS) model [ 19 ], cellular automata (CA) model [ 20 ], the conversion of land use and its effects at a small regional extent (CLUE-S) model [ 21 ], and a future land use simulation (FLUS) model [ 22 ], etc. The FLUS model, first proposed by Liu et al [ 14 ], can effectively deal with the complexity and uncertainty of the conversion of various land use types under the mutual influence of the human-land relationship.…”
Section: Introductionmentioning
confidence: 99%
“…With the development and application of computer science and geographic information system (GIS) technology, research on land use spatial layout simulation models has rapidly increased [ 15 , 16 , 17 , 18 ]. Researchers have used a variety of simulation models to simulate future land use in terms of the quantitative characteristics and spatial layout, including a multi-agent system (MAS) model [ 19 ], cellular automata (CA) model [ 20 ], the conversion of land use and its effects at a small regional extent (CLUE-S) model [ 21 ], and a future land use simulation (FLUS) model [ 22 ], etc. The FLUS model, first proposed by Liu et al [ 14 ], can effectively deal with the complexity and uncertainty of the conversion of various land use types under the mutual influence of the human-land relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that reclamation had become one of the most widespread threats to coastal wetlands, which seriously affected the structure, function and service of coastal ecosystems [28]. In positive human-driven processes, restoration had an impact on the change in blue carbon storage, which also reflected that the ecological restoration project under human intervention could effectively weaken the negative impact of reclamation on CBCS [7,29].…”
Section: Spatiotemporal Change and Driving Processes Of Cbcsmentioning
confidence: 99%
“…Agentes são entidades computacionais autônomas de processamento de informações, que atuam a partir de estímulos e sensores do ambiente (Russell e Norvig, 2002). Assim, a tomada de decisão e as interações dos agentes geram mudanças no ambiente, que afetam suas percepções e decisões (She et al, 2017). Ao simular computacionalmente um MAS temse uma Simulação Baseada em Multiagente (Multi-Agent Based Simulation -MABS), que possibilita descrever o comportamento de sistemas complexos com múltiplos domínios (Gilbert e Troitzsch, 2005).…”
Section: Introductionunclassified